2010
DOI: 10.1155/2010/130519
|View full text |Cite
|
Sign up to set email alerts
|

Late-Term Elective Abortion and Susceptibility to Posttraumatic Stress Symptoms

Abstract: The primary aim of this study was to compare the experience of an early abortion (1st trimester) to a late abortion (2nd and 3rd trimester) relative to Posttraumatic Stress Disorder (PTSD) symptoms after controlling for socio-demographic and personal history variables. Online surveys were completed by 374 women who experienced either a 1st trimester abortion (up to 12 weeks gestation) or a 2nd or 3rd trimester abortion (13 weeks gestation or beyond). Most respondents (81%) were U.S. citizens. Later abortions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
2
23
1
1
Order By: Relevance
“…Earlier studies have suggested that having an abortion at later gestational ages is more traumatic than having an abortion in the first trimester of pregnancy. 32 37 Our findings did not support this notion. The lack of statistically significant baseline differences between the Near-limit and First-trimester abortion groups, the less steep decline in symptoms experienced by women in the First-trimester group than women in the Near-limit group, and the greater proportion of First-trimester than Near-limit women with symptoms and at risk of PTSD at year 4, suggests that having an abortion later in pregnancy does not place women at greater risk of adverse mental health outcomes than having an abortion earlier in pregnancy.…”
Section: Discussioncontrasting
confidence: 81%
“…Earlier studies have suggested that having an abortion at later gestational ages is more traumatic than having an abortion in the first trimester of pregnancy. 32 37 Our findings did not support this notion. The lack of statistically significant baseline differences between the Near-limit and First-trimester abortion groups, the less steep decline in symptoms experienced by women in the First-trimester group than women in the Near-limit group, and the greater proportion of First-trimester than Near-limit women with symptoms and at risk of PTSD at year 4, suggests that having an abortion later in pregnancy does not place women at greater risk of adverse mental health outcomes than having an abortion earlier in pregnancy.…”
Section: Discussioncontrasting
confidence: 81%
“…Earlier studies have suggested that having an abortion later in the pregnancy can result in more adverse mental health outcomes for women than having a first-trimester abortion 27 or that the evidence is too scarce to draw conclusions. 2 In our study, for all but 1 outcome, women in the near-limit and first-trimester groups exhibited similar levels and trajectories of mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that these inconsistent findings can be explained in part by the findings of Coleman, Coyle, and Rue (2010), who determined that trauma symptoms' incidence is greater when abortion occurs during the 2nd or 3rd pregnancy trimester. Based on these findings, our results may be explained by the fact that our participants had abortions mainly during the 1st pregnancy trimester, more specifically around the 9th week of pregnancy.…”
Section: Discussionmentioning
confidence: 96%